Aetiological classification and prognosis in patients with heart failure with preserved ejection fraction. (29th November 2021) - Fayol, Antoine; Wack, Maxime; Livrozet, Marine; Carves, Jean‐Baptiste; Domengé, Orianne; Vermersch, Eva; Mirabel, Mariana; Karras, Alexandre; Le Guen, Julien; Blanchard, Anne; Azizi, Michel; Amar, Laurence; et al.
Abstract: Aims: Heart failure with preserved ejection fraction (HFpEF) is a heterogeneous syndrome with various causes that may influence prognosis. Methods and results: We extracted the electronic medical records for 2180 consecutive patients hospitalized between 2016 and 2019 for decompensated heart failure. Using a text mining algorithm looking for a left ventricular ejection fraction ≥50% and plasma brain natriuretic peptide level >100 pg/mL, we identified 928 HFpEF patients. We screened for a prevailing cause of HFpEF according to European guidelines and found that 418 (45.0%) patients had secondary HFpEF due to either myocardial ( n  = 125, 13.5%) or loading condition abnormalities ( n  = 293, 31.5%), while the remaining 510 (55.0%) patients had idiopathic HFpEF. We assessed the association between the causes of HFpEF and survival collected up to 31 December 2020 using Cox proportional hazards analysis. Even though patients with idiopathic HFpEF were older, frequently female, and had frequent co‐morbidities and a higher crude mortality rate compared with secondary HFpEF patients, their prognosis was similar after adjustment for age and sex. Unsupervised clustering analysis revealed three main phenogroups with different distribution of idiopathic vs. secondary HFpEF. The phenogroup with the highest proportion of idiopathic HFpEF (69%) had (i) an excess rate of non‐cardiac co‐morbidities including chronic obstructive pulmonary disease (31%) or obesity (41%) and (ii) a better prognosis compared with the two other phenogroups enriched with secondary HFpEF. Conclusions: Aetiological classification provides clinical and prognostic information and may be useful to better decipher the clinical heterogeneity of HFpEF. Condensed abstract: The identification of specific aetiologies was possible in almost half of patients with heart failure with preserved ejection fraction (HFpEF). Compared with patients with secondary HFpEF, patients with idiopathic HFpEF were older, frequently female, and had a higher proportion of co‐morbidities and high crude mortality rates, but their prognosis was similar after adjustment for age and sex. Unsupervised cluster analysis, however, indicated that idiopathic HFpEF patients were mostly grouped into separate cluster with a better prognosis. Aetiological classification provides clinical and prognostic information and may be useful to better decipher the clinical heterogeneity of HFpEF.